Az esély - Trencsényi, Klára (Hungary : Titánia Master Pro, 2007)
”I had a bit of a cold, and all of a sudden I fell off the bed, paralyzed. I'd had a stroke... When I recovered months later, I was fired from my job”, says forty-year-old Kata, the most cheerful member of the group. The others – also participants in the reintegration project run by the Pécs-based company UWYTA – face cancer, post-cancer recovery, mental problems or simply ”socialization disadvantages”. After the change of the political regime in Hungary hundreds of workplaces were closed down, and many people working in heavy industry or mining were made redundant. They haven’t been able to find a new job since. Our documentary focuses on a European Union-financed project launched in autumn 2006 under the name ‘Social Change = Chance’. It follows those who joined, their hopes, the program’s daily activities, its difficult and more successful moments. But in the end the project itself is threatened...
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films